2003
DOI: 10.1111/j.1151-2916.2003.tb03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Macroporous Alumina with Tailored Porosity

Abstract: Macroporous alumina materials were fabricated via colloidal processing using polymer spheres as the template and ceramic particles as the building blocks. The influence of the suspension conditions and volume ratio of the polymer/ceramic particles on the formation of the pore structure has been investigated. The results showed that the suspension conditions have a significant effect on the pore morphology. A well‐defined three‐dimensional, ordered porous structure with a controllable pore size and porosity cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 18 publications
4
61
0
5
Order By: Relevance
“…The textured porous aalumina bodies were prepared by the slip casting of welldispersed aalumina suspensions followed by heating at 1073 K. The relative density of the calcined bo Special Issue ''Innovative Ceramics (I)'' dies without polymer addition was 60.7÷, but that with the polymer addition 61) decreased to 55÷. Figure 23 shows the XRD patterns of the infiltrated porous bodies initially with and without polymer addition and reaction sintering at 1973 K. The sample was confirmed to be balumina by the reaction of aalumina and Na 2 O, but aalumina did remain when the polymer particle was not added to alumina, but when the polymer was added, the residual aalumina decreases.…”
Section: Process Factors and Microstructure Controlmentioning
confidence: 99%
“…The textured porous aalumina bodies were prepared by the slip casting of welldispersed aalumina suspensions followed by heating at 1073 K. The relative density of the calcined bo Special Issue ''Innovative Ceramics (I)'' dies without polymer addition was 60.7÷, but that with the polymer addition 61) decreased to 55÷. Figure 23 shows the XRD patterns of the infiltrated porous bodies initially with and without polymer addition and reaction sintering at 1973 K. The sample was confirmed to be balumina by the reaction of aalumina and Na 2 O, but aalumina did remain when the polymer particle was not added to alumina, but when the polymer was added, the residual aalumina decreases.…”
Section: Process Factors and Microstructure Controlmentioning
confidence: 99%
“…5 (indicated by dotted lines) shows that they intersect in the region of 2 g/cm 3 , indicating the possibility of a non-shrink ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolation of these curves showed that they intersect with the values of density of about 2 g/cm 3 , which indicates the possibility of producing non-shrink ceramics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These macroporous ceramic coating layer also requires control of pore sizes, shapes and pore size distributions in order to design preferred physical and chemical properties, such as size effect, electric affinity. [2][3][4][5][6][7][8] Recently, porous ceramic materials with highly controlled macroporous structures have been prepared by a colloidal crystal templating technique using some monodisperse microspheres such as polystyrene, poly methyl methacrylate, and silica. [2][3][4][5][6][7][8] However, it is difficult to obtain porous materials with well-ordered macroporous structure onto a solid substrate for short fabrication time.…”
Section: Introductionmentioning
confidence: 99%